1 Introduction
A finite sequence
$\mathbf {k}=(k_1,\ldots ,k_n)$
of positive integers is called an index. The weight, depth and height of the index
$\mathbf {k}$
are defined respectively by
$k_1{\kern-1.5pt}+\cdots +k_n$
, n and the cardinality
$|\{\,j\mid 1\leq j\leq n, k_j\geq 2\}|$
. If
$k_1>1$
, the index
$\mathbf {k}$
is called admissible. For an admissible index
$\mathbf {k}=(k_1,\ldots ,k_n)$
, the multiple zeta value
$\zeta (\mathbf {k})$
and the multiple zeta-star value
$\zeta ^{\star }(\mathbf {k})$
are defined respectively by
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu1.png?pub-status=live)
A systematic study of multiple zeta values was carried out by Hoffman [Reference Hoffman2] and Zagier [Reference Zagier, Joseph, Mignot, Murat, Prum and Rentschler10]. More results of multiple zeta values can be found in the book [Reference Zhao11] of Zhao.
We focus on Ohno–Zagier type relations. For nonnegative integers
$k,n,s$
, denote by
$I_0(k,n,s)$
the set of admissible indices of weight k, depth n and height s. It is easy to see that
$I_0(k,n,s)$
is nonempty if and only if
$k\geq n+s$
and
$n\geq s\geq 1$
. Using the Gaussian hypergeometric function, Ohno and Zagier proved in [Reference Ohno and Zagier7] that
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu2.png?pub-status=live)
where
$\alpha $
and
$\beta $
are determined by
$\alpha +\beta =u+v$
and
$\alpha \beta =w$
. Similar studies were carried out on various generalisations of multiple zeta values. For example, Aoki et al. [Reference Aoki, Kombu and Ohno1] gave a similar formula for the sums of multiple zeta-star values involving the generalised hypergeometric function
${}_3F_2$
:
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu3.png?pub-status=live)
with
$\alpha $
and
$\beta $
determined by
$\alpha +\beta =u+v$
and
$\alpha \beta =uv-w^2$
. Here, for a positive integer m and complex numbers
$a_1,\ldots ,a_{m+1},b_1,\ldots ,b_m$
with
$b_1,\ldots ,b_m\neq 0,-1,-2,\ldots ,$
the generalised hypergeometric function
${}_{m+1}F_m$
is defined by
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu4.png?pub-status=live)
with the Pochhammer symbol
$(a)_n$
defined by
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu5.png?pub-status=live)
It is known that this formal power series converges absolutely for
$|z|<1$
, and it also converges absolutely for
$|z|=1$
if
$\Re (\sum b_i-\sum a_i)>0$
. If
$m=1$
, we get the Gaussian hypergeometric function.
In [Reference Takeyama9], Takeyama studied the Ohno–Zagier type relation for a level two variant of multiple zeta values, called multiple T-values, introduced by Kaneko and Tsumura [Reference Kaneko, Tsumura, Mishou, Nakamura, Suzuki and Umegaki6]. As a consequence, a weighted sum formula of multiple T-values with fixed weight and depth was given in [Reference Takeyama9]. We consider another level two variant of multiple zeta values, called multiple t-values, introduced by Hoffman in [Reference Hoffman3].
For an admissible index
$\mathbf {k}=(k_1,\ldots ,k_n)$
, the multiple t-value
$t(\mathbf {k})$
and the multiple t-star value
$t^{\star }(\mathbf {k})$
are defined respectively by
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu6.png?pub-status=live)
It is easy to obtain the following iterated integral representations:
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu7.png?pub-status=live)
where
$({dt}/{t})^{k_i-1}={{dt}/{t}\cdots {dt}/{t}}\ (k_i-1 \mbox { factors})$
, and for one-forms
$\omega _i(t)=f_i(t)dt$
,
$i=1,2,\ldots ,k$
, we define the iterated integral
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu8.png?pub-status=live)
We want to study the sum of multiple t-(star) values with fixed weight, depth and height. For nonnegative integers
$k,n,s$
, define
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu9.png?pub-status=live)
Then we obtain Ohno–Zagier type relations which represent the generating functions of
$G_0(k,n,s)$
and
$G_0^{\star }(k,n,s)$
by the generalised hypergeometric function
${}_3F_2$
.
Theorem 1.1. For formal variables
$u,v,w$
,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu10.png?pub-status=live)
where
$\alpha $
and
$\beta $
are determined by
$\alpha +\beta {\kern-1pt}={\kern-1pt}1-\frac{1}{2}u+\frac{1}{2}v$
and
$\alpha \beta {\kern-1pt}={\kern-1pt}\tfrac 14(1{\kern-1pt}-{\kern-1pt}u+v- uv+w)$
.
Theorem 1.2. For formal variables
$u,v,w$
,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu11.png?pub-status=live)
where
$\alpha ^{\star }$
and
$\beta ^{\star }$
are determined by
$\alpha ^{\star }+\beta ^{\star }=3-\frac{1}{2}u-\frac{1}{2}v$
and
$\alpha \beta =\tfrac 14(9-3u-3v+uv-w)$
.
From these theorems and using summation formulae for
$\,_3F_2$
, we obtain several corollaries in Section 2. For example, we give a formula for the generating function of sums of multiple t-(star) values of maximal height and a weighted sum formula of sums of multiple t-(star) values with fixed weight and depth. Finally, we prove Theorems 1.1 and 1.2 in Section 3.
2 Applications
2.1 Sums of height one
To save space, we denote a sequence of k repeated n times by
$\{k\}^n$
.
Setting
$w=0$
in Theorem 1.1,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu12.png?pub-status=live)
Hence, we get the following result, which gives the generating function of height one multiple t-values.
Corollary 2.1 [Reference Hoffman3, Theorem 5.1]
We have
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu13.png?pub-status=live)
Similarly, setting
$w=0$
in Theorem 1.2,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu14.png?pub-status=live)
Therefore, we obtain the generating function of height one multiple t-star values.
Corollary 2.2. We have
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu15.png?pub-status=live)
Note that using [Reference Hoffman3, Lemma 5.2], for any integer
$m\geq 2$
,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu16.png?pub-status=live)
2.2 Sums of maximal height
Setting
$v=0$
in Theorem 1.1, we get the generating function of sums of multiple t-values of maximal height. By the symmetric sum formula [Reference Hoffman3, Theorem 3.2], the sum of multiple t-values with fixed weight, depth and maximal height can be represented by t-values. Here we give a closed formula for the generating function of the sums of maximal height.
Corollary 2.3. For formal variables
$u,w$
,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqn1.png?pub-status=live)
where x and y are determined by
$x+y=u$
and
$xy=w$
.
Proof. Setting
$v=0$
in Theorem 1.1, we get
$\alpha +\beta =1-\frac{1}{2}u$
and
$\alpha \beta =\tfrac 14(1-u+w)$
. Let
$x=1-2\alpha $
and
$y=1-2\beta $
, then
$x+y=u$
and
$xy=w$
. Using the summation formula [Reference Prudnikov, Brychkov and Marichev8, 7.4.4.28],
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqn2.png?pub-status=live)
With
$a=\alpha $
,
$b=\beta $
and
$c=\tfrac 32$
,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu17.png?pub-status=live)
Using the duplication formula
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu18.png?pub-status=live)
and the expansion
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqn3.png?pub-status=live)
where
$\gamma $
is Euler’s constant,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu19.png?pub-status=live)
Since
$t(n)=(1-2^{-n})\zeta (n)$
, we find that (see also [Reference Hoffman3, Theorem 3.3])
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqn4.png?pub-status=live)
Now it is easy to finish the proof.
Similarly, we have a formula for the generating function of the sums of multiple t-star values of maximal height.
Corollary 2.4. For formal variables
$u,w$
,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqn5.png?pub-status=live)
where
$x^{\star }$
and
$y^{\star }$
are determined by
$x^{\star }+y^{\star }=u$
and
$x^{\star }y^{\star }=-w$
.
Proof. Setting
$v=0$
in Theorem 1.2, we obtain
$\alpha ^{\star }+\beta ^{\star }=3-\frac{1}{2}u$
and
$\alpha ^{\star }\beta ^{\star }=\tfrac 14 (9-3u-w)$
. Let
$x^{\star }=3-2\alpha ^{\star }$
and
$y^{\star }=3-2\beta ^{\star }$
, so that
$x^{\star }+y^{\star }=u$
and
$x^{\star }y^{\star }=-w$
. Using the summation formula (2.2) with
$a=\frac{1}{2}(1-u)$
,
$b=\tfrac 12$
and
$c=\alpha ^{\star }$
,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu20.png?pub-status=live)
Now the result follows from (2.4).
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu21.png?pub-status=live)
Also, setting
$u=0$
in (2.1) and (2.5),
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu22.png?pub-status=live)
These formulae can also be deduced from the identities [Reference Ihara, Kajikawa, Ohno and Okuda4, Reference Ihara, Kaneko and Zagier5]
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu23.png?pub-status=live)
in the harmonic shuffle algebra.
2.3 A weighted sum formula
Let
$I_0(k,n)$
be the set of admissible indices of weight k and depth n, and define
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu24.png?pub-status=live)
which are the sums of multiple t-values and multiple t-star values with fixed weight k and depth n, respectively. By setting
$w=uv$
and then
$v=2u$
or
$v=-2u$
in Theorems 1.1 and 1.2, we obtain the following results.
Proposition 2.5. For a formal variable u,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqn6.png?pub-status=live)
Proof. If
$w=uv$
in Theorem 1.1,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu25.png?pub-status=live)
Hence, we get the expression for the generating function of sums of multiple t-values with fixed weight and depth:
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu26.png?pub-status=live)
Setting
$v=2u$
,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu27.png?pub-status=live)
Using Dixon’s summation formula [Reference Prudnikov, Brychkov and Marichev8, 7.4.4.21]: for
$\Re (a-2b-2c)>-2$
,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu28.png?pub-status=live)
with
$a=1$
,
$b=\tfrac 12$
and
$c=\frac{1}{2}(1+u)$
, we get
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu29.png?pub-status=live)
Then using (2.3), (2.4), the relation
$\zeta (n)=(1-2^{-n})^{-1}t(n)$
and
$t(2)={\pi ^2}/{8}$
, we get
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu30.png?pub-status=live)
Similarly, setting
$w=uv$
in Theorem 1.2,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu31.png?pub-status=live)
Hence,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu32.png?pub-status=live)
Let
$v=-2u$
. Then
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu33.png?pub-status=live)
Now it is easy to finish the proof.
Expanding the right-hand side of (2.6) gives the following weighted sum formula.
Corollary 2.6. For any integer
$k\geq 2$
,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu34.png?pub-status=live)
3 Proofs of Theorems 1.1 and 1.2
The proofs of Theorems 1.1 and 1.2 are similar to that of the Ohno–Zagier relation for multiple zeta values in [Reference Ohno and Zagier7].
As in [Reference Hoffman3], for an index
$\mathbf {k}=(k_1,\ldots ,k_n)$
, define
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu35.png?pub-status=live)
Then
$\mathcal {L}_{\mathbf {k}}(z)$
and
$\mathcal {L}_{\mathbf {k}}^{\star }(z)$
converge absolutely for
$|z|<1$
. If
$k_1>1$
,
$\mathcal {L}_{\mathbf {k}}(1)=t(\mathbf {k})$
and
$\mathcal {L}_{\mathbf {k}}^{\star }(1)=t^{\star }(\mathbf {k})$
. From [Reference Hoffman3, Lemma 5.1],
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqn7.png?pub-status=live)
Similarly,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqn8.png?pub-status=live)
One can also obtain (3.1) and (3.2) from the following iterated integral representations:
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu36.png?pub-status=live)
3.1 Proof of Theorem 1.1
For nonnegative integers
$k,n,s$
, denote by
$I(k,n,s)$
the set of indices of weight k, depth n and height s, and define the sums
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu37.png?pub-status=live)
If the index set is empty, the sum is treated as zero. We also set
$G(0,0,0;z)=1$
. Note that if
$k\geq n+s$
and
$n\geq s\geq 1$
,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu38.png?pub-status=live)
For integers
$k,n,s$
, using (3.1), we have the following identities:
-
(1) if
$k\geq n+s$ and
$n\geq s\geq 1$ ,
(3.3)$$ \begin{align} \frac{d}{dz} & G_0(k,n,s;z) \nonumber\\ & =\frac{1}{z}[G(k-1,n,s-1;z)+G_0(k-1,n,s;z)-G_0(k-1,n,s-1;z)]; \end{align} $$
-
(2) if
$k\geq n+s$ ,
$n\geq s\geq 0$ and
$n\geq 2$ ,
(3.4)$$ \begin{align} \frac{d}{dz}[G(k,n,s;z)-G_0(k,n,s;z)]=\frac{z}{1-z^2}G(k-1,n-1,s;z). \end{align} $$
We define the generating functions
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu39.png?pub-status=live)
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu40.png?pub-status=live)
Eliminating
$\Phi (z)$
, we obtain the differential equation satisfied by
$\Phi _0(z)$
.
Proposition 3.1.
$\Phi _0=\Phi _0(z)$
satisfies the following differential equation:
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqn11.png?pub-status=live)
We want to find the unique power series solution
$\Phi _0(z)=\sum _{n=1}^\infty a_nz^n$
. From (3.5), we see that
$a_1={1}/({1-u})$
,
$a_2=0$
and
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu41.png?pub-status=live)
Hence, for any
$n\geq 1$
, we have
$a_{2n}=0$
and
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu42.png?pub-status=live)
Since
$(\alpha -1)+(\,\beta -1)=-1-\frac{1}{2}u+\frac{1}{2}v$
and
$(\alpha -1)(\,\beta -1)=\tfrac 14(1+u-v-uv+w)$
,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu43.png?pub-status=live)
Therefore, we can represent
$\Phi _0(z)$
by the generalised hypergeometric function
$\,_3F_2$
as displayed in the following theorem.
Theorem 3.2. We have
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu44.png?pub-status=live)
3.2 Proof of Theorem 1.2
Similarly, for nonnegative integers
$k,n,s$
, we define the sums
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu45.png?pub-status=live)
with
$G^{\star }(0,0,0;z)=1$
. Using (3.2), we have the following identities:
-
(1) if
$k\geq n+s$ and
$n\geq s\geq 1$ ,
(3.6)$$ \begin{align} &\frac{d}{dz} G_0^{\star}(k,n,s;z)\nonumber\\ &\quad =\frac{1}{z}[G^{\star}(k-1,n,s-1;z)+G_0^{\star}(k-1,n,s;z)-G_0^{\star}(k-1,n,s-1;z)]; \end{align} $$
-
(2) if
$k\geq n+s$ ,
$n\geq s\geq 0$ and
$n\geq 2$ ,
(3.7)$$ \begin{align} \frac{d}{dz}[G^{\star}(k,n,s;z)-G_0^{\star}(k,n,s;z)]=\frac{1}{z(1-z^2)}G^{\star}(k-1,n-1,s;z). \end{align} $$
We define the generating functions
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu46.png?pub-status=live)
Then using (3.2), (3.6) and (3.7),
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu47.png?pub-status=live)
Eliminating
$\Phi ^{\star }(z)$
, we get the differential equation satisfied by
$\Phi _0^{\star }(z)$
.
Proposition 3.3.
$\Phi _0^{\star }=\Phi _0^{\star }(z)$
satisfies the following differential equation:
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqn14.png?pub-status=live)
Assume that
$\Phi _0^{\star }(z){\kern-1pt}={\kern-2pt}\sum _{n=1}^\infty{\kern-1pt} a_n^{\star }z^n$
. Using (3.8), we find that
$a_1^{\star }{\kern-1pt}={\kern-1pt}{1}/({1{\kern-1pt}-{\kern-1pt}u{\kern-1pt}-{\kern-1pt}v+uv{\kern-1pt}-{\kern-1pt}w})$
,
$a_2^{\star }=0$
and
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu48.png?pub-status=live)
Hence, for any
$n\geq 1$
, we have
$a_{2n}^{\star }=0$
and
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu49.png?pub-status=live)
Therefore, we have the following theorem.
Theorem 3.4. We have
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20230305132902986-0639:S0004972722001198:S0004972722001198_eqnu50.png?pub-status=live)